Correlations among anti‐Müllerian hormone levels, body mass index and lipid profile in reproductive‐aged women: The Korea Nurses' Health Study. Issue 6 (2nd August 2021) - Lim, Sarah; Kim, Sue; Kim, Oksoo; Kim, Bohye; Jung, Heeja; Ko, Kwang‐Pil; Lee, Hyangkyu
Abstract: Aim: This study aimed to evaluate the correlations among anti‐Müllerian hormone levels, body mass index and lipid profile in female nurses of reproductive age. Design: This is a descriptive cross‐sectional study that used data from the Korea Nurses' Health Study, based on Nurses' Health Study 3 in the United States. Methods: Participants included 448 female nurses of reproductive age. They provided details about their work experience, shift work, body mass index and history of polycystic ovary syndrome. Serum anti‐Müllerian hormone levels and lipid profile were measured using blood samples. Statistical analysis included quantile regression analysis using STATA 13.0. Data were collected between November 2016 and March 2017 from Module 5 of the Korean Nurses' Health Study. Results: Approximately 12% of the participants were underweight, and roughly one‐tenth were either overweight or obese. Although linear regression showed no relationship between anti‐Müllerian hormone levels and body mass index, quantile regression showed that body mass index, total cholesterol levels and low‐density lipoprotein levels were negatively correlated with anti‐Müllerian hormone levels at the lower tails of the dependent variable. Meanwhile, high‐density lipoprotein levels were positively correlated with anti‐Müllerian hormone at the higher percentiles of anti‐Müllerian hormone levels. Conclusion: These findings suggest the possibility that changes in the lipid profile may influence anti‐Müllerian hormone levels in women with diminished ovarian function, rather than obesity itself.